Wavelet transform associated with the q-Dunkl Operator - Bettaibi, Neji; Bettaieb, Rym H.; Bouaziz, Slim (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we present some new elements of harmonic analysis related to the q-Dunkl operator introduced in [1}, we define and study the q-wavelets and the continuous q-wavelet transforms associated with this operator. Next, as an application, we give inversion formulas for the q-Dunkl intertwining operator and its dual using q-wavelets.